Extramedular lesions of a small intestinum in acute myeloid leukemia: case report and literature review - I. A. Dokshina; A. V. Lyanguzov; S. V. Ignatyev; O. Yu. Sergunina; S. L. Kalinina; E. S. Prokopyev; D. A. Dyakonov (Онкогематология, 2019)
Currently, the diagnosis of acute myeloid lekemia is based on the standards of morphological studies and immunophenotyping of the bone marrow. The manifestation of the disease can be accompanied by extramedullary lesions, which are difficult to verify. The article presents a case of diagnosis of acute myeloid lekemia in an elderly w oman, occurring with a leukemic lesion of the small in - testine. Morphological studies and immunophenotyping of small intestine biopsy revealed acute myeloid lekemia blast tumor cells. Difficulties of examination in such cases lead to late revealing of leukemic infiltrates of rare localization and significantly worsen the prognosis.